2019
DOI: 10.3389/fneur.2019.00029
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Subthalamic Nucleus Stimulation in Parkinson's Disease: Optimal Frequency for Gait Depends on Stimulation Site and Axial Symptoms

Abstract: Axial symptoms emerge in a significant proportion of patients with Parkinson's disease (PD) within 5 years of deep brain stimulation (STN-DBS). Lowering the stimulation frequency may reduce these symptoms. The objectives of the current study were to establish the relationship between gait performance and STN-DBS frequency in chronically stimulated patients with PD, and to identify factors underlying variability in this relationship. Twenty-four patients treated chronically with STN-DBS (>4 years) were studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Axial motor symptoms can be improved in some patients, remain unchanged in others, or even worsen in a subset of patients after DBS (Xie et al, 2012;Pötter-Nerger and Volkmann, 2013;Collomb-Clerc and Welter, 2015;Di Giulio et al, 2019). Several factors can affect axial symptoms, including patient characteristics, DBS target, the precise positioning of the electrode within the nucleus and also the stimulation parameters (Tisch et al, 2007;Fasano et al, 2015;Ramirez-Zamora and Ostrem, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Axial motor symptoms can be improved in some patients, remain unchanged in others, or even worsen in a subset of patients after DBS (Xie et al, 2012;Pötter-Nerger and Volkmann, 2013;Collomb-Clerc and Welter, 2015;Di Giulio et al, 2019). Several factors can affect axial symptoms, including patient characteristics, DBS target, the precise positioning of the electrode within the nucleus and also the stimulation parameters (Tisch et al, 2007;Fasano et al, 2015;Ramirez-Zamora and Ostrem, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a systematic varying of stimulation frequency in small steps has shown that only a limited number of frequencies robustly improve movement amplitude in a tapping task, and that even small frequency deviations can drastically reduce efficacy ( Huang et al ., 2014 ). Similarly, Di Giulio et al . (2019) showed peaked DBS frequency tuning curves in gait performance.…”
Section: Discussionmentioning
confidence: 68%
“…The only criterion that stood out was that the patients in the responding group had a stimulation frequency of either 80 or 100 Hz, slightly lower than the conventional stimulation frequency of 130 Hz for STN DBS (Moro et al, 2002). This is interesting considering that several studies suggest that lowering the frequency can be beneficial for improving gait problems in some patients (di Biase & Fasano, 2016;Di Giulio et al, 2019;Xie et al, 2018).…”
Section: Discussionmentioning
confidence: 99%